2007
DOI: 10.1016/j.virol.2007.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profile of Rous Sarcoma Virus transformed chicken embryo fibroblasts reveals new signaling targets of viral-src

Abstract: Transformation of chicken fibroblasts in vitro by Rous Sarcoma Virus represents a model of cancer in which a single oncogene, viral src, uniformly and rapidly transforms primary cells in culture. We experimentally surveyed the transcriptional program affected by Rous Sarcoma Virus (RSV) in primary culture of chicken embryo fibroblasts. As a control, we used cells infected with non-transforming RSV mutant td106, in which the src gene was deleted. Using Affymetrix GeneChip Chicken Genome Arrays, we report 811 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 68 publications
3
22
0
Order By: Relevance
“…In fact, our study showed that the PLAU transcript was upregulated 196 ( þ /À 69)-fold, using Affymetrix Gene Chip arrays. We confirmed this result by a more precise measurement using real-time PCR tests on two independently isolated RNA samples as 42 ( þ /À11)-fold upregulation (Masker et al, 2007). Independently from our group, the laboratory of Pierre-Andre Bedard also documented that the PLAU transcript was the most robustly upregulated gene in RSV-transformed CEFs, being more than 44-fold increased over the level detected in non-transformed controls (Maslikowski et al, 2010).…”
Section: Viral Src Induces Plau Gene At the Level Of Transcriptionsupporting
confidence: 75%
See 3 more Smart Citations
“…In fact, our study showed that the PLAU transcript was upregulated 196 ( þ /À 69)-fold, using Affymetrix Gene Chip arrays. We confirmed this result by a more precise measurement using real-time PCR tests on two independently isolated RNA samples as 42 ( þ /À11)-fold upregulation (Masker et al, 2007). Independently from our group, the laboratory of Pierre-Andre Bedard also documented that the PLAU transcript was the most robustly upregulated gene in RSV-transformed CEFs, being more than 44-fold increased over the level detected in non-transformed controls (Maslikowski et al, 2010).…”
Section: Viral Src Induces Plau Gene At the Level Of Transcriptionsupporting
confidence: 75%
“…This work was reported by the laboratory of Edward Reich at The Rockefeller University in New York City, and later confirmed by numerous publications from various laboratories (Sudol, 1985;Bell et al, 1990;Leslie et al, 1990). More than three decades later, with the completion of the sequencing of mouse and chicken genomes and the subsequent availability of Affymetrix GeneChip genome arrays (Affymetrix, Santa Clara, CA, USA), several laboratories, including our team, have surveyed the transcriptional program affected by the RSV transformation (Masker et al, 2007;Maslikowski et al, 2010). We, and others, have confirmed the transcriptional induction of the PLAU gene and showed that it is the most highly upregulated transcript (Masker et al, 2007;Maslikowski et al, 2010).…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…They identified significant overexpression of DNA methyltransferase 1 in v-Src-transfected fibroblasts, whereas several tumor suppressor genes were downregulated by v-Src, but could be reexpressed after treatment with a demethylating agent. A similar analysis was carried out by Masker et al 42 using chicken embryo fibroblasts transfected with Rous Sarcoma virus. They observed 811 genes modulated by v-Src.…”
Section: Discussionmentioning
confidence: 78%